Line lists for the b1Σ+-X3Σ− and a1Δ-X3Σ− transitions of SO. (September 2021) - Bernath, Peter F.; Johnson, Ryan; Liévin, Jacques
Highlights: Line lists for bands of the SO b 1 Σ + -X 3 Σ − and a 1 Δ-X 3 Σ − transitions. Transition dipole moment functions are based on ab initio calculations. SO line lists are useful for the atmospheres of IO and Venus. Abstract: SO is found in many astronomical sources such as the atmospheres of Io and Venus. In order to create more complete line lists, we fit spectroscopic data on SO from the literature using PGOPHER. The fits covered v = 0 to v = 6 for the X 3 Σ − state, v = 0–5 for the a 1 Δ state and v = 0–2 for b 1 Σ + state. LeRoy's RKR program was used to produce pointwise potential energy curves. High level ab initio calculations, including spin-orbit coupling, were carried out to obtain the electric transition dipole moment functions for the nominally forbidden b 1 Σ + -X 3 Σ − and a 1 Δ-X 3 Σ − transitions. The RKR potentials and transition dipole moment points were input into LeRoy's LEVEL program to calculate the transition dipole matrix elements for all possible b-X and a-X bands. For the b 1 Σ + -X 3 Σ − transition, the electric and magnetic transition dipole matrix elements were scaled using the experimental values obtained by Setzer et al. [J Mol Spectrosc 1999;198:163–174] for the 0–0 band. The transition dipole moment matrix elements were used in PGOPHER to produce our line lists for all possible bands of the b 1 Σ + -X 3 Σ − and a 1 Δ-X 3 Σ − transitions.